Towards continuous brain monitoring: a pilot qualitative study of user experiences with in-ear EEG - Chirag Haria; Benjamin H. L. Harris; Louis J. Koizia; Michael B. Fertleman (Frontiers in Digital Health, 2026)
Introduction In-ear electroencephalography (EEG) is an emerging form of wearable neurotechnology that offers the potential for continuous and unobtrusive brain monitoring outside traditional clinical settings. While technical feasibility has been demonstrated across applications including seizure detection, sleep monitoring, and cognitive assessment, little is known about how users experience and perceive this technology. This pilot study aimed to explore user experiences of in-ear EEG and identify factors influencing its acceptability and adoption. Method A qualitative study was conducted using semi-structured interviews with ten participants following exposure to an in-ear EEG device. Interviews were audio-recorded, transcribed verbatim, and analysed using an inductive approach guided by Braun and Clarke's reflexive thematic analysis. Results Five interrelated themes were identified: embodied acceptability, pragmatic usability, reframing EEG from clinical procedure to personal technology, conditional adoption, and future integration into everyday life. Participants described the device as comfortable, unobtrusive, and comparable to familiar consumer technologies such as earbuds. Compared with conventional scalp EEG, in-ear EEG was viewed as more flexible, discreet, and compatible with everyday activities. However, willingness to adopt the technology remained conditional on demonstrating clinical accuracy comparable to traditional EEG systems. Participants also anticipated applications in long-term and ambulatory monitoring. Discussion In-ear EEG was perceived as a highly acceptable and practical form of wearable brain monitoring. Adoption appeared to be facilitated by familiarity and integration into everyday life, but remained dependent on confidence in diagnostic performance. These findings highlight the importance of combining technical validation with user-centred design to support implementation of wearable neurotechnology and real-world monitoring of brain function.